Inventarisasi pengetahuan lokal hutan pesisir di Tatar Karang Tasikmalaya - Samson CMS; Atwar Bajari; Dadang Sugiana; Muhammad Ilham (Faculty of Communication, Padjadjaran University, 2023)
Local knowledge of an area doesn't exist without reason; it has an accompanying purpose and philosophy. There are certainly goals and philosophies behind the local knowledge that the Tatar Karang community of Tasikmalaya District holds. This research aims to understand the local knowledge of the coastal forests of the Tatar Karang community. This study uses a qualitative descriptive approach with methods of observation, in-depth interviews, and literature studies. It is organized based on the cultural inventory structure of Kemendikbud 2016 and the SECI Model. Informants in this research include traditional elders, customary stakeholders, village heads, cultural figures, religious figures, community leaders, youth leaders, and leaders of traditional families. The results of the study indicate that: 1) Historically, the coastal forest is a heritage of the customary system that existed long before 1861 and was implemented as a legal system in place at the time; 2) Conceptually, the coastal forest serves as a protective measure for residents from various natural disaster threats originating from the direction of the ocean; 3) Factually, the condition of the coastal forest is quite concerning due to land use conversion policies, resulting in much of its area being damaged; and 4) Strategies for preserving the coastal forest can be done through: 1) the SECI Model analysis, which includes socialization, externalization, combination, and internalization. This ensures that stakeholders, traditional internal parties, can supervise objectively; 2) maximizing the cultural approach through developing three traditions: hajat lembur, marak, and rarangkén huma; and 3) a popular method using new media. In conclusion, preserving this intangible cultural heritage is vital and, at the very least, should be done through inventory. Thus, this tacit knowledge heritage can be documented.